(untitled) (Prithvi Journal of Research and Innovation, 2025)
The purpose of this study was to evaluate the bacteriological quality of ready-to-eat (RTE) instant noodles and their accompanying seasonings vended in local marketplaces of Pokhara, Nepal. A total of 66 samples, comprising 33 instant noodle packages and thirty-three seasoning sachets from eleven different brands (A, B, C, D, E, F, G, H, I, J and K) were analysed for bacterial contamination using Plate Count agar to enumerate total viable bacteria. Among the noodle samples, brand A exhibited the highest contamination level with a bacterial count of 3.03 × 105 CFU/gram, followed by brand C with bacterial count of 2.99×105 CFU/gram. For the seasonings, brand K had the highest level of contamination with a bacterial count of 1.65×106 CFU/gram, followed by the seasoning from brand A with count of 8.97 × 105 CFU/gram. Of the total 59 bacterial isolates obtained, 94.92% were gram-positive, including Staphylococcus aureus (44.1%), Bacillus spp (32.2%), and Coagulase negative Staphylococci (CoNS) (18.6%) and gram-negative bacteria represented by only Klebsiella spp (5.1%). Antibiotic susceptibility tests (AST) showed that all the isolates of CoNS, Klebsiella species, and Staphylococcus aureus were 100% susceptible to Co-Trimoxazole, Gentamicin, Doxycycline, and Chloramphenicol. All isolates obtained exhibited complete resistance to Ampicillin, whereas Klebsiella spp isolates also showed resistance to Azithromycin. These findings revealed a significant microbial load and antibiotic-resistant bacteria in RTE instant noodles, highlighting the need for improved hygiene practices and regular monitoring of microbial and antibiotic resistance patterns in ready-to-eat instant noodles, particularly in the seasoning sachets, to safeguard public health.